A Preliminary Assessment of Land-to-Water Surface Area Ratios (LWR) for Sustainable Land Use in Aquaculture. (2nd April 2016) - Jescovitch, Lauren N.; Chaney, Philip L.; Boyd, Claude E.
ABSTRACT: Several organizations have developed eco-label certification programs with standards to conserve resources and reduce negative environmental impacts of fish and shrimp production. Production by pond aquaculture is reported on a water surface area basis, but additional land for embankments, roads, storage areas, and so on, is required. Thus, data on total land use by aquaculture farms are needed for formulating land use standards. Preliminary investigation of land-to-water surface area ratios (LWRs) based on analysis of 100 aquaculture farms (2, 783 ponds) in twenty-six countries using satellite imagery (Google Earth Pro) was conducted. The LWR declined with increasing pond size to around 5.0 ha before stabilizing at 1.25. Average LWR was 1.48. Variations in LWR were noted among climate zones and continents. Jenks optimization revealed five LWR classes, and most LWR values were below 1.89. Results of this study could be helpful in developing land use standards for aquaculture ecolabel certification.